Medical students’ perception regarding health policy teaching and their participation in health policy roles: A survey at a public university in Malaysia - Haque, Mainul; A. Rahman, Nor Azlina; Rahman, Sayeeda; Majumder, Md Anwarul Azim; Syed Mohdhar, Sharifah Shasha; Lugova, Halyna; Abdullah, Adnan; Abdullah, Shahidah Leong; Ismail, Mohd Hafizi; Charan, Jaykaran; Kumar, Santosh; Irfan, Mohammed; et al. (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Abstract: Background: Health policy is a set of comprehensive principles and legislations that guide how healthcare should be effectively delivered in the community. Medical schools should prepare students to undertake managerial responsibilities by incorporating health policy into the curriculum to deal with the intricacies of healthcare systems and their clinical roles in their future professional careers. Objective: To examine medical students’ perception at a Public University in Malaysia regarding teaching health policy and their participation in health policy roles. Material and Methods: A cross-sectional study using universal sampling was carried out among the medical students using a paper-based questionnaire to collect the data. Results: Most respondents opined their willingness to learn health policy (80.9%) and that teaching health policy (83.6%) should be compulsory for medical students. The respondents thought health policy should be introduced earlier in Year 1 or 2. The student scores on their knowledge regarding health policy and year of study were significantly associated with their involvement in the health policy roles in both the simple and multiple logistic regression. Both statistical tests reported higher participation in health policy roles with the higher year of study, though only Year 4 and 5 were significant in the simple logistic regression and only Year 5 in the multiple logistic regression compared to Year 1. On the other hand, age and type of admission show significant results only in the simple logistic regression, while the race was only significant at the multivariate level. Conclusions: This study demonstrated that most respondents showed their willingness to learn health policy, participate in the health policy programs, and recommend that health policy be considered an essential topic in the medical curriculum, which should be taught right from the first year of medical school. We recommend encouraging students’ participation in health policy activities.